The game simulation method in the control of logistics supply (Journal of Economic Research & Business Administration, 2016)
This article examines the simulation game from the perspective of the theory of control of organizational systems. The theory of control of organizational systems (TСOS) studies the mechanisms of functioning of organizational systems. The main research method – mathematical modeling (system analysis, game theory, decision theory, operations research) management decision-making procedures. The results are used in practice in the management of organizations of all sizes – from the production halls, to the industry and the region. The article aims to provide specialists in the theory and practice of organizational systems management (researchers, teachers, graduate students, as well as the real managers, managers) show TСOS use to describe the conflict in logistics systems. We describe the existing contradictions in logistics. The classification TСOS basic management mechanisms for all management functions in relation to logistics systems. In the numerical example analyzes the centralized supply scheme with the principle of use of rigid centralization.
Keywords: game theory; simulation; organizational system; mechanism of control.